Survey of the exocrine system in protanilla wallacei(Hymenoptera, Formicidae) - Hashim, Rosli; Ito, F.; Billen, J.; Bauweleers, E. (2013)
We studied the exocrine system of both workers and ergatoid queens of Protanilla wallacei using light, scanning and transmission electron microscopy. Our survey revealed the presence of 26 glands, of which 6 had never been found before in ants. Five of these represent novel discoveries for social insects in general. The overall novel discoveries comprise an epithelial stipes gland, a pharyngeal wall gland, a central petiole gland, a lateral postpetiole gland and a foot-sole gland in the hindleg pretarsi. The intramandibular epithelial gland was already reported in some bees previously, but is now for the first time also reported in ants. The exocrine system of workers and ergatoid queens is very similar, with only the spermathecal gland showing an obvious difference. This is in line with the limited anatomical as well as behavioural difference between both castes in Protanilla compared to the situation in Leptanilla. (C) 2013 Elsevier Ltd. All rights reserved.